Age and Sequence of Permanent Teeth Eruption in Lebanese Children - Nahla Nassif; Elia Sfeir (The Scientific World Journal)
Background. The timing of eruption of permanent teeth can be a precious help to the pediatric practitioner in identifying an appropriate treatment plan. Usually, it presents a more precise sign of an early or late growth of the child. Aims. It is to determine whether the timing of the permanent teeth eruption in Lebanese pediatric population can be considered as standard Lebanese values, since no other study was previously performed. Materials and Methods. A cross-sectional study is conducted, and the clinical emergence data are collected for a sample of 2317 Lebanese children aged between 5.5 years and 13 years (1129 girls and 1188 boys) from different socioeconomic groups in rural and urban communities spread over different regions in Lebanon. The study investigates dental emergence patterns. Results. Statistical analysis is performed with the SPSS Software. A confidence interval of 95% and significance level of 5% are adopted. The trend is for males to begin their permanent teeth eruption later than girls. Emergence of all permanent mandibular teeth is earlier than maxillary ones. Symmetry is found between the right and left teeth in the maxilla, as well as in the mandibula. Conclusion. In this study, the results indicate that premolars and second permanent molars erupt earlier in the Lebanese children compared to children of other countries reflected in several studies.